Maintenance and risk management of rockfall protection net fences through numerical study of damage influence (Fracture and Structural Integrity, 2017)
Rockfall protection net fences are key protection systems in mountainous areas worldwide to ensure the safety of infrastructures, roads and urban areas. Maintenance of these products is fundamental for public administrations in order to guarantee risk mitigation. This paper deals with the assessment of the installation problems and damages induced by ageing of rockfall protection net fences, using numerical modelling in order to evaluate the influence of these issues on their behavior. A percentage of the residual efficiency is assessed as a useful tool for risk analysis and maintenance planning.
Keywords: Rockfall protection net fence; Rockfall; Explicit numerical modelling; Residual risk; Maintenance